The contribution of Grozny oil educational institutions to the formation of an engineering and tech-nical stratum in the structure of Chechen society (1920-1930s) - Muslim M. Murdalov; Lema A. Turpalov (Кавказология, 2024)
The policy of indigenization in national regions initiated by the Bolshevik Party in the 1920s and 1930s assumed, along with the creation of written languages, the transfer of schools and office work to native languages, the formation of a social stratum of the proletariat and engineering and technical workers from among the indigenous inhabitants. This problem was especially acute in Chechnya, although a powerful oil industry complex had formed on its territory as early as the end of the 18th century. However, due to restrictions associated with the ongoing Caucasian War, the indigenous people did not have access to industries and enterprises. Another obstacle was the mass illiteracy of the highlanders, which deprived them of the opportunity to study in educational institutions in Russia. The policy of the tsarist administration also did not contribute to the spread of education in the region. The lag of the Chechens in the field of education manifested itself during the period of restoration of the national economy after the destructive revolutions and civil war. In particular, this applied to the Grozny oil industry, which was of great importance for the economy of the entire country. Meanwhile, the implementation of the recovery program was hampered by an acute shortage of qualified personnel: foreign specialists left the country, as did a significant portion of engineers and workers resettled from Russian provinces. The situation around training specialists from indigenous nationalities began to change only with the establishment of Soviet power. The Bolshevik program of indigenization assumed the formation of a layer of workers and engineering and technical workers in the national regions, who would become the support of Soviet power in the region. The system of oil educational institutions established in the 1920s made it possible in many respects to train specialists from among the indigenous nationalities, which helped to change the ethno-social structure of Grozny.